Efeitos de diferentes tipos de entrevista na acurácia de relato verbal de crianças - Faria, Camila de Paula (Universidade Federal de São Carlos, 2023)
Studies on verbal and non-verbal correspondence can be considered of great importance since reporting has a determining role in various contexts. This study focused on the forensic context, more specifically, on investigative interviews with children, and replicated the study of Sparling et al. (2011) with the purpose of investigating, from a behavioral perspective, the effects of different types of interviews (suggestive questions, repeated questions, and questions with co-witness information) on children's verbal report accuracy. Four children aged between seven and nine years participated. Children were exposed to a baseline condition, which evaluated the accuracy of the report using in a closed-question interview (“yes” or “no” answers), without the use of any of the interview techniques employed in this study. Children were then exposed to three other conditions, involving different types of interviews (suggestive questions; repeated questions and questions with information from co-witnesses) conducted by a female interviewer. A mixed design of non-concurrent multiple baseline across participants and adapted alternating treatment was employed. The results showed transient effects of interview types and variability among participants. The lowest accuracy rates were observed in P1 for questions with co-witness information; in P2 for suggestive questions and in P3 for repeated questions. P4 participant remained showing high rates of accurate responses in all experimental conditions. In general, these results replicated the findings of Sparling et al. (2011), indicating that the effect of the type of interview may vary for each individual. The need for studies with single subject designs and the possible effects of the online implementation of the procedure were discussed.
Effects of different types of interviews on children's verbal report accuracy
Keywords: Correspondência verbal; Crianças; Entrevista investigativa; Relato verbal; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA EXPERIMENTAL